1997
DOI: 10.1046/j.1365-2575.1997.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of an executive information system: a case study

Abstract: The progress of an executive information system project within a manufacturing organization over a period of 9 years is described. The case study illustrates the importance of the interaction between the business environment, the organizational environment and the perceptions and interpretations of events and facts by stakeholders on the success or failure of an information system. It shows the importance of context in the development and implementation of an executive information system and the dynamic nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Alternatively, a list may be presented in the form of success factors rather than failure factors (DeLone and McLean, ). Other approaches have applied contingency theory (Poulymenakou and Holmes, ; McBride, ), organizational learning (Beynon‐Davies et al ., ; Irani et al , , Fortune and Peters, ), chaos theory (McBride, ), agency theory (Devos et al , ) and the social construction of technology (Bartis and Mitev, ). Failure occurs because of factors such as bad project management, inadequate contract management, lack of top management support, lack of business involvement, poor quality assurance and inability to manage expectations.…”
Section: Information Systems Failure Studiesmentioning
confidence: 99%
“…Alternatively, a list may be presented in the form of success factors rather than failure factors (DeLone and McLean, ). Other approaches have applied contingency theory (Poulymenakou and Holmes, ; McBride, ), organizational learning (Beynon‐Davies et al ., ; Irani et al , , Fortune and Peters, ), chaos theory (McBride, ), agency theory (Devos et al , ) and the social construction of technology (Bartis and Mitev, ). Failure occurs because of factors such as bad project management, inadequate contract management, lack of top management support, lack of business involvement, poor quality assurance and inability to manage expectations.…”
Section: Information Systems Failure Studiesmentioning
confidence: 99%
“…Espejo (1993) also looked at the limitations of EIS. McBride (1997) studied an organization where an executive information system was seen initially as a success but a failure in the long run. However, Seeley & Targett's (1997) study revealed that senior executives (particularly younger ones) are making more extensive use of computers with a wider range of software.…”
Section: Information Systems Practicementioning
confidence: 99%
“…Arnott (2008) conducted a meta-review of a number of studies including McBride (1997), Poon and Wagner (2001), Salmeron and Herrero (2005), Sammon and Finnegan (2000), and Wixom and Watson (2001) that investigated the success of BI, Data Warehouse, and Executive Information Systems (EIS).…”
Section: Introductionmentioning
confidence: 99%